A régiók és az állam konfliktusai az innovációs kormányzásban : az innováció központi és regionális irányítása Magyarországon - Gál, Zoltán (Közép-Európai Közlemények, 2013)
The paper deals with the evolving systems of central and regional govenance of innovation during the past two decades in Hungary. It examines the management of innovation, the organizational structure and institutions of innovation policy placing innovation in the development strategies of central governments. It discusses the reasons why the fully decentralised systems of regional innovation has not developed and what led to the weakening the regional innovation systems despite once the ground-breaking legistlation.